A multigram-scale lower E-factor procedure for MIBA-catalyzed direct amidation and its application to the coupling of alpha and beta aminoacids1. Issue 7 (6th July 2015) - Fatemi, Solmaz; Gernigon, Nicolas; Hall, Dennis G.
<x xml:space="preserve">Abstract</x> More economical conditions for direct amidation between amines and carboxylic acids, including α- and β-amino acids, have been optimized using the MIBA catalyst (5-methoxy-2-iodophenylboronic acid, 6).